Effect of Using Intensive Reading Strategy on Students’ Vocabulary Achievement at the First Year Student - Yemima Debora Saragih; Yugi Diraga Prawiyata (Education & Learning, 2023)
This research aimed to determine whether intensive reading strategy is effective to increase students’ English vocabulary. This research used quantitative method as its design.  The population in this research consists of 40 students from SMA Swasta EKLESIA. The sample of this research was 20 students in experimental group and 20 students in control group. To collect the data from both classes, this research used pre-test and post-test. The data from both classes analyzed by using SPSS program to calculate and determine the validity of the data. Based on the data analysis, the result of T-test revealed that the post-test score of the experimental group was higher than control group. Additionally, the result of hypothesis analysis showed that t-test is higher than t-table (2.831 > 2.021). It indicated that H0 (Null Hypothesis) was rejected and Ha (Alternative Hypothesis) was accepted. Based on the result of this research, it showed that there was significant improvement on students’ vocabulary achievement in using intensive reading as a strategy in teaching.